Evaluation of the sensitizing potential of food proteins using two mouse models. (16th November 2016) - Smit, Joost; Zeeuw-Brouwer, Mary-lène de; van Roest, Manon; de Jong, Govardus; van Bilsen, Jolanda
Highlights: Most assays used for the risk assessment of novel proteins show false positive results for low/non-allergens. A DC-T cell assay and a mouse model were able to distinguish 5 known allergens from 5 low/non-allergens. This method to identify the allergenic risk of new or modified proteins. This method may also elucidate the mechanism of sensitization to food proteins or to improve diagnostics and immunotherapy of food allergy. Abstract: The current methodology to identify allergenic food proteins is effective in identifying those that are likely to cross-react with known allergens. However, most assays show false positive results for low/non-allergens. Therefore, an ex vivo/in vitro DC-T cell assay and an in vivo mouse model were used to distinguish known allergenic food proteins (Ara h 1, β-Lactoglobulin, Pan b 1, bovine serum albumin, whey protein isolate) from low/non allergenic food proteins (soy lipoxygenase, gelatin, beef tropomyosin, rubisco, Sola t 1). CD4+ T cells from protein/alum-immunized mice were incubated with corresponding protein-pulsed bone marrow-derived DC and analyzed for cytokine release. All known allergens induced Th2 responses in vitro, whereas soy lipoxygenase, gelatin or beef tropomyosin did not. Sola t 1 and rubisco induced a more generalized T cell response due to endotoxin contamination, indicating the endotoxin-sensitivity of the DC-T assay. To analyze responses in vivo, mice were orally sensitized on days 0 and 7. Known allergens induced IgE and mMCP-1 release upon oral challenge at day 16, whereas the low/non-allergens did not. Both the DC-T cell assay and the mouse model were able to distinguish 5 known allergens from 5 low/non-allergens and may be useful to identify novel allergenic food proteins.